The Influence of Brand Image, Promotion, and Product Quality on Purchase Intention at Mahkota Brownies Store, Tuban - Jazman Azim; M.Yaskun; Abid Muhtarom (Sean Institute, 2024)
This study aims to analyze the influence of brand image, promotion, and product quality on consumer buying interest in Toko Mahkota Brownies Tuban. The research uses an explanatory quantitative approach with a survey method. The research population is 2,312 consumers who made purchases at the Tuman Brownies Crown Store in the period from October to December 2023. Samples were determined using the Slovin formula with an error rate of 10% so that 96 respondents were obtained, and the sampling technique used random sampling. Primary data were collected through a Likert scale questionnaire and analyzed using multiple linear regression with the help of IBM SPSS. The results showed that brand image had a positive and significant effect on buying interest (t = 2.831; sig. = 0.006), promotion had a positive and significant effect on buying interest (t = 2.353; sig. = 0.021), and product quality had a positive and significant effect on buying interest (t = 4.088; sig. = 0.000). Simultaneously, brand image, promotion, and product quality had a significant effect on buying interest (F = 10.785; sig. = 0.000). The Adjusted R Square value of 0.509 indicates that the three independent variables are able to explain 50.9% of the variation in buying interest. Based on the standardized beta value, product quality is the variable with the strongest relative influence. These findings affirm the importance of strengthening product quality, brand image, and consistent promotion to increase consumer buying interest.